Highly reduced graphene oxide supported Pt nanocomposites as highly efficient catalysts for methanol oxidation1. Issue 12 (11th February 2015) - Feng, Hongbin; Liu, Yong; Li, Jinghong
<x xml:space="preserve">Abstract</x> The highly reduced graphene oxide by solvated electrons supported Pt nanocomposites shows highly efficient catalytic activity for methanol oxidation.